Analysis and modelling of momentum transport based on NBI modulation experiments at ASDEX Upgrade. (1st May 2022) - Zimmermann, C F B; McDermott, R M; Fable, E; Angioni, C; Duval, B P; Dux, R; Salmi, A; Stroth, U; Tala, T; Tardini, G; Pütterich, T; ,; et al.
Abstract: The prediction of plasma rotation is of high interest for fusion research due to the effects of the rotation upon magnetohydrodynamic (MHD) instabilities, impurities, and turbulent transport in general. In this work, an analysis method was studied and validated to reliably extract momentum transport coefficients from neutral beam injection (NBI) modulation experiments. To this end, a set of discharges was created with similar background profiles for the ion and electron temperatures, the heat fluxes, the electron density, and the plasma rotation that, therefore, should exhibit similar momentum transport coefficients. In these discharges, a range of temporal perturbations were imposed by modulating and varying the power deposition of the NBI, electron-cyclotron-resonance heating (ECRH), and ion-cyclotron-resonance heating (ICRH). The transport model including diffusion, convection, and residual stress was implemented within the ASTRA code. The Prandtl number P r = χ φ / χ i was assessed via the GKW code. A convective Coriolis pinch was fitted and the intrinsic torque from the residual stress was estimated. The obtained transport coefficients agree within error bars for sufficiently small imposed temperature perturbations, as would be expected, from the similar background profiles. This successful validation of the methodology opens the door to study the parametric dependence of the diffusive and convective momentum transport of the main ions of the plasma as well as the turbulent intrinsic torque in a future work.